The circadian system of African mole-rats : behavioural activity rhythms and early gene expression ( c-fos ) in the suprachiasmatic nucleus - Bennett, Nigel Charles (University of Pretoria, 2013)
Dissertation (MSc (Zoology))--University of Pretoria, 2005.